Using the School Environmental Education Programme (SEEP) to Decolonise the Curriculum: Lessons from Ufasimba Primary School in South Africa. Issue 1 (2nd January 2019) - Zimu-Biyela, Nomusa
Abstract: The topic of decolonisation has become a contested terrain because of the curriculum challenges facing education systems in Africa, particularly South Africa. To address these challenges, many scholars have underscored the importance of using socio-culturally relevant curricula in Africa. This article is divided into two sections. First, it explores challenges facing education systems in Africa and how decolonisation and socio-culturally relevant curricula, resources, and teacher training can provide answers to those challenges. Then the article explains how Ufasimba Primary School emerged as a school where the School Environmental Education Programme (SEEP) was used to decolonise the curriculum. The challenge, however, was that the Department of Basic Education (DBE) in the KwaZulu- Natal province in South Africa had not made it mandatory for schools to implement the SEEP. This study recommends that the integration of the SEEP into the curriculum should be mandatory at primary education level. A qualitative approach and a grounded theory method, underpinned by the social constructivist paradigm, were used for this study. Data collection methods included semi-structured interviews and the observation method. The basic principles of grounded theory and the NVivo software program assisted in the data analysis for this study.